Factors Affecting Health Tourism Promotion for the Elderly in Nakhon Nayok Province, Thailand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research were 1) to study health tourism behaviors of the elderly tourists and 2) to analyzefactors affecting health tourism promotion for the elderly in Nakhon Nayok Province. The samples were 400 elderly touristsvisiting health tourism attractions in Nakhon Nayok randomized by convenience sampling. The research instrument was aquestionnaire and analyzed by frequency, percentage, mean, standard deviation, correlation coefficient, and multiple regression.The research results indicated that health tourism behaviors of the elderly were at a high level in all aspects: knowledge of healthtourism, skills for tourism, and attitudes toward tourism. Tourism based on natural farming, organic farming, and the new theoryagriculture in accordance with His Majesty’s initiative were the most demanded. Moreover, the results revealed that there shouldbe promoting tourist attractions of abundant nature and biodiversity, such as agro tourism attractions, culture attractions, creativetourism attractions, and natural health tourism. Regarding hypothesis testing, demographic differences, namely, age, educationand income, affected health tourism promotion for the elderly at the statistically significant level of .05. Tourism behaviors ofthe elderly were positively related to health tourism promotion: knowledge of health tourism (r=0.480), skills for tourism(r=0.282), and attitudes toward tourism (r=0.517). Based on the results of multiple regression analysis, knowledge of healthtourism and attitudes toward tourism affected health tourism promotion for the elderly, and the predictive equation was Y =1.075 + 0.246X1 + 0.370X2.